Literackie obrazy socjalistycznej Warszawy i frankistowskiego Madrytu w perspektywie geopoetyki i komparatystyki. Przykład powieści Zły Leopolda Tyrmanda i Ul Camilo José Celi - Rombel, Maria (Tematy i Konteksty, 2019)
The paper aims to juxtapose the literary portrayals of the socialist Warsaw and Francoist Madrid depicted in two postwar novels: The Man with the White Eyes by Leopold Tyrmand and The Hive by Camilo José Cela1, respectively. The starting point for the considerations is geopoetics and, more precisely, the concept of the sensory and emotive topographies. It is intended to demonstrate that the approach in question provides the tools adequate to analyse the configuration of Warsaw’s and Madrid’s urban spaces portrayed in Polish novels from the Polish People’s Republic period and Spanish novels from the Francoism period. The comparative approach, in turn, enables the juxtaposing of the research objects and gathering of the data useful for the purposes of Polish-Spanish intercultural studies, such as intercultural communication studies.